Differences between Financial Systems in Europe: Consequences for EMU - Reinhard H. Schmidt (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 1999)
Major differences between national financial systems might make a common monetary policy difficult. As within Europe, Germany and the United Kingdom differ most with respect to their financial systems, the present paper addresses its topic under the assumption that the United Kingdom is already a part of EMU. Employing a comprehensive concept of a financial system, the author shows that there are indeed profound differences between the national financial systems of Germany and the United Kingdom. But he argues that these differences are not likely to create great problems for a common monetary policy. In the context of the present paper, one important difference between the two financial systems refers to the structure of the respective financial sector and, as a consequence, to the strength with which a given monetary policy impulse set by the central bank is passed on to the financial sector. The other important difference refers to the typical relationship between the banks and the business sector in each country which determines to what extent the financial sectors and especially the banks pass on pressure exerted on them by a monetary policy authority to their clients in their national business sector. In Germany, the central bank has a stronger influence on the financial sector than in England, while, for systemic reasons, German banks tend to soften monetary policy pressures on their customers more than British banks do. As far as the transmission of a restrictive monetary policy of the ECB to the real economy is concerned, these two differences tend to offset each other. This is good news for the advocates of a monetary union as it eases the task of the ECB when it comes to determining the strength of its monetary policy measures.
urn:nbn:de:hebis:30-16599
Keywords: E51; E58; G20; 330; European Monetary Union; Financial Systems; Transmission Mechanism; Eurozone; Finanzsystem; Finanzsektor; Geldpolitische Transmission; Geldpolitik; EU-Staaten; Großbritannien; Deutschland